Application of pharmacoeconomics to formulary management in a health system setting. (21st February 2019) - Studdert, Ann L; Gong, Cynthia L; Srinivas, Sandy; Chin, Alexander L; Deresinski, Stan
Abstract: Purpose: A novel value-based approach to evaluate costly specialty drugs for formulary addition was developed. Summary: In February 2016, Stanford Health Care launched the specialty drug subcommittee (SDSC), a subcommittee of the pharmacy and therapeutics committee, responsible for the formulary review of specialty pharmaceuticals. A process was developed for value-based review that includes not only consideration of clinical trial data and institutional acquisition costs but also internal patient outcomes and a cost-effectiveness model using internal financial data. A Markov model was developed to assess the value of trabectedin, which was approved for formulary addition in April 2016, relative to the addition of dacarbazine. The economic model and internal patient outcome analysis were presented to the prescribing oncologist and the SDSC for review. Internal data revealed that fewer patients than had been estimated received trabectedin, with outcomes significantly worse than those observed in the clinical trial leading to Food and Drug Administration approval. In the cost-effectiveness model, trabectedin had higher costs and poorer outcomes compared with dacarbazine. Based on the economic model, low utilization, and real-world outcomes, trabectedin was removed from formulary and a restrictive treatment pathway for nonformulary use, developed by the primary prescriber, was implemented. This process has since been applied to 11 more specialty drugs. Conclusion: Internal cost-effectiveness models in combination with real-world patient outcomes data can be effective formulary management tools. Engagement and collaboration with the requesting provider are key to developing thoughtful treatment pathways.